2015
DOI: 10.4066/amj.2015.2240
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous aspiration versus catheter drainage of liver abscess: A retrospective review

Abstract: The null hypothesis that both PA and PCD are equally effective in the drainage of liver abscess cannot be rejected. Apart from PA being simpler and safer to perform, the higher incidence of indwelling catheter-associated complications suggests that a trial of PA should always be attempted first.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Klebsiella pneumoniae liver abscess is a rare and emerging infectious disease in patients in Asia, the United States, and Europe, and it tends to spread globally [ 23 ]. In the majority of these liver abscesses, the etiology cannot be established, thus these abscesses are characterized as cryptogenic [ 24 ]. Since Klebsiella pneumoniae strains may colonize the human gastrointestinal tract, translocation from the gastrointestinal tract is the most likely route by which Klebsiella pneumoniae causes formation of liver abscesses [ 15 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Klebsiella pneumoniae liver abscess is a rare and emerging infectious disease in patients in Asia, the United States, and Europe, and it tends to spread globally [ 23 ]. In the majority of these liver abscesses, the etiology cannot be established, thus these abscesses are characterized as cryptogenic [ 24 ]. Since Klebsiella pneumoniae strains may colonize the human gastrointestinal tract, translocation from the gastrointestinal tract is the most likely route by which Klebsiella pneumoniae causes formation of liver abscesses [ 15 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that diabetes mellitus (DM) can be an important predisposing factor that correlates with a high incidence of K1 serotype liver abscesses due to neutrophil dysfunction and chemotaxis failure [ 25 , 26 ], and that the incidence rate of metastatic infections is higher in patients with DM [ 23 , 24 ]. Metastatic infections are a clinical, diagnostic, and therapeutic challenge and are only diagnosed in one third of the cases on admission [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous abscess drainage has a success rate of up to 100%[ 46 ], hence making it the first line drainage technique. On the other hand percutaneous drainage is associated with side effects including catheter dislodgment, subscapsular hematoma, drainage from catheter exit site[ 47 ], hepato-venous fisulas[ 48 ] and hepato-colic fistulas[ 49 ]. In recent years, EUS guided drainage for liver abscesses has emerged an alternative approach since it was first proposed by Seewald et al[ 50 ] in 2005.…”
Section: Therapeutic Use Of Eus In Liver Abscessesmentioning
confidence: 99%
“…Inadvertent puncture of intervening bowel loops, solid organs or vasculature can lead to peritonitis, bleeding, infection and, rarely, even death. 2 Additionally, percutaneous access via the flanks or buttocks can be a source of constant discomfort, pain, and can adversely impact patient quality of life. Furthermore, multi-loculated and complex collections may require prolonged drainage thereby predisposing to skin infection, fistula formation and may require multiple catheter exchange procedures to correct drain dysfunction resulting in prolonged hospital stay.…”
Section: P Ostoperative Abdominal Fluid Collectionsmentioning
confidence: 99%